Fracture and fragmentation : towards a politics of the nation in midnight's children and shame - Yeo, Gideon Peng Khiam (2015)
The idea of the nation is one that has traditionally been informed by a study of history. However, when discourses of history are investigated, they appear to be given over to stark bias, duplicity. More importantly, there is no proper way in which one can unproblematically know something, and our own readerly assumptions and worldview ought to be questioned. The thesis will argue that the dialogical encounter between historical texts and historical fiction raises questions on the inherent flaws within the official narratives of history, thus informing us of the difficulty of apprehending the idea of the nation. When plurality and multiplicity surface through the cracks of this encounter, it appears that it is only through fragments that we can apprehend and work towards a form of wholeness. Through his novels, Rushdie appears to push for a negotiation between the opposing ideas of singularity and plurality, fragmentation and wholeness in order to present a worldview that is both nuanced and balanced.